Estoque de carbono e estabilidade de agregados de um latossolo vermelho distrófico, sob diferentes manejos - Rozane, Danilo Eduardo [UNESP]; Centurion, Jose Frederico; Romualdo, Liliane Maria; Kenji Taniguchi, Carlos Alberto; Trabuco, Milaine; Alves, Adriana Ursulino (Universidade Federal de Uberlândia (UFU), 2010)
These systems of soil use and management are very important in carbon supply and stability of aggregates, because affect directly culture yields. The aim of this project is to evaluate the carbon supply and stability of Haplustox aggregates under different managements. It was utilized a completely randomized experimental design in split plot scheme, with six replications. Thus, the treatments utilized were three different soil managements ( native forest, pasture with Tanzania grass and corn). The plots were consisted by three layers (0-10; 10-20 and 20-30 cm) and were analyzed to determined the organic matter, organic carbon supply of soil ( layers and equivalent soil mass methods) and weighed average diameter (DMP) and geometrical average diameter (DMG). The results indicated that the evaluated managements systems affected the size of soil aggregates of the ground and in its distribution in the layer of 0-30 cm of depth. The greatest accumulation of carbon were in the surface layers, although, there were not variation between the management systems.

Os sistemas de uso e manejo dos solos são fatores preponderantes no estoque de carbono e na estabilidade dos agregados, que exercem grandes influências na produtividade das culturas. A presente pesquisa teve como objetivo avaliar o estoque de carbono e a estabilidade de agregados de um Latossolo Vermelho Distrófico, sob diferentes usos e manejos. O delineamento experimental utilizado foi inteiramente casualizado, em parcelas subdivididas, com seis repetições. Assim, foram consideras utilizadas como tratamentos principais três manejos de solo (mata nativa, pastagem com ‘capim Tanzânia’ e cultivo com milho) e, como subparcelas, três camadas (0-10; 10-20 e 20-30cm). As amostras de solo foram analisadas para determinação da matéria orgânica, estoque de carbono orgânico no solo (métodos de camada e de massa de solo equivalente) e o diâmetro médio ponderado (DMP) e o diâmetro médio geométrico (DMG). Os resultados indicam que os sistemas de manejo avaliados influenciaram nos tamanhos dos agregados do solo e em sua distribuição no perfil do solo. O maior acúmulo de C se deu nas camadas superficiais, apesar de não haver variação entre os sistemas de manejo.
Carbon supply and stability of haplustox aggregates under different managements
Keywords: Soil quality; soil organic carbon; DMG; DMP